Colloquial Polish : the complete course for beginners - Mazur, Bolesław W. (Colloquial series., 2001)
This new edition of the best-selling Polish course for beginners has been completely rewritten to make learning the language easier and more enjoyable than before. Written by an experienced teacher and author, Colloquial Polish offers a step-by-step approach to the language as it is spoken and written today. No previous knowledge of Polish is required. Features include:* Lively dialogues* Lots of exercises with full answer key* Jargon-free grammar notes and a quick reference grammar* Extensive Polish-English and English-Polish word listsWith all.